2020
DOI: 10.1186/s40634-020-00287-x
|View full text |Cite
|
Sign up to set email alerts
|

Ramp lesions: a systematic review of MRI diagnostic accuracy and treatment efficacy

Abstract: Purpose We conducted a systematic review of the published literature to assess the accuracy of Magnetic Resonance Imaging (MRI) in establishing the presence of ramp lesions (RLs) in Anterior Cruciate Ligament (ACL) deficient knees and the clinical efficacy of the surgical repair of RLs. Methods A comprehensive search of the MEDLINE, Web of Science and Scopus databases was performed according to PRISMA guidelines. Studies assessing MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…The preoperative diagnosis of ramp lesions is difficult. There are currently no effective clinical tests or signs allowing to detect these lesions and magnetic resonance imaging (MRI) has been reported to have a poor sensitivity [26]. A systematic review of MRI diagnostic accuracy reported a pooled sensitivity of 65.1% (95% CI 59.7 to 70.4%) based on 9 studies [26].…”
Section: Introductionmentioning
confidence: 99%
“…The preoperative diagnosis of ramp lesions is difficult. There are currently no effective clinical tests or signs allowing to detect these lesions and magnetic resonance imaging (MRI) has been reported to have a poor sensitivity [26]. A systematic review of MRI diagnostic accuracy reported a pooled sensitivity of 65.1% (95% CI 59.7 to 70.4%) based on 9 studies [26].…”
Section: Introductionmentioning
confidence: 99%
“…Functional outcome score (The International Knee Documentation Committee (IKDC) score) was obtained and considered the main clinical outcome variable. The IKDC evaluation form is a validated instrument to record the clinical state of ACL reconstructed patients at one time [ 27 , 28 ]. The IKDC scores form was used to measure QOL in our statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Acute ACL tear is associated with meniscal injuries in more than 50% of subjects, and in more than 80% of chronic ACL tear cases. Medial meniscus is firmly attached to the tibia and femur, acting as a knee stabilizer, and preventing anterior translation, especially in the ACL-deficient knee, thus being especially susceptible to injuries [3].…”
Section: Introductionmentioning
confidence: 99%